Deforestación y sedimentación en los manglares del Golfo de Urabá. Síntesis de los impactos sobre la fauna macrobéntica e íctica en el delta del río Turbo (2013)
ABSTRACT: This synthesis relates deforestation and land use change in coastal plain of the Turbo River watershed and impacts upon estuarine fauna in its delta. This watershed is shown within the context of hidroclimatological (rainfall and discharge) variability across the eastern margin of Urabá Gulf. Coastal-plain forest conversion rate to crops were quantiF ed, as a possible explanation of increased sediment transport to the river and the nearshore. Despite of the expansion of the delta, mangrove area was reduced as a consequence of conversion to crops and pastures. The dominant mangrove snail Neritina virginea was reduced in density in anthropogenic forest gaps and edges, as well as in pastures, due to altered microhabitats, and can be therefore used as a bio-indicator. The high sedimentation rates seem to be responsible for the faunistic poverty of the benthos, but do not seem responsible of deleterious effects on the dominant species. The diversity and abundance of F shes was greatly altered by high sedimentation near the river mouth. ±inally, social features of the human communities were related to landscape changes. Herewith, we reported on the current ecosystem status, as the baseline for proposing management and conservation guidelines in order to prevent and restore impacts on mangroves and the coastal zone in this region.